Editorial - International Journal of Sustainable Energy Planning and Management Vol 30 - Østergaard, Poul Alberg; Johannsen, Rasmus Magni (International Journal of Sustainable Energy Planning and Management, 2021)
This editorial introduces the main findings from the 30th Volume of the International Journal of Sustainable Energy Planning and Management. This volume probes into analyses of the technical interactions between multi-energy carrier energy hubs and the role and feasibility of cogeneration of heat and power in a Portuguese context. It moves on to analyse the framework for implementing photo voltaic technology and decision processes for implementing PV technology. Lastly, it presents work on the role of renewable energy sources in meeting carbon dioxide emission reduction goals in Iran.